2009
DOI: 10.1124/mol.109.058677
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Brain Penetrant Neuropeptide Y Y2 Receptor Antagonists Discovered by Whole-Cell High-Throughput Screening

Abstract: The role of neuropeptide Y Y2 receptor (Y2R) in human diseases such as obesity, mood disorders, and alcoholism could be better resolved by the use of small-molecule chemical probes that are substantially different from the currently available Y2R antagonist,Presented here are five potent, selective, and publicly available Y2R antagonists identified by a high-throughput screening approach. These compounds belong to four chemical scaffolds that are structurally distinct from the peptidomimetic BIIE0246. In funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 42 publications
2
57
0
1
Order By: Relevance
“…Our results showed that 1) Y2 receptor blockade reversed the anorexic response to iv infusion of PYY(3-36) but did not increase food intake when administered alone; 2) Y1 and Y5 receptor antagonists neither attenuated PYY(3-36)-induced anorexia nor altered food intake when given alone; and 3) Y2 receptor blockade attenuated anorexic responses to gastric infusions of lower doses of casein hydrolysate and long-chain triglycerides but not to maltodextrin infusions. Previous work showed that Y2 antagonist BIIE 0246 does not penetrate the blood-brain barrier (13). Together, these results support the hypothesis that gut PYY(3-36) action at Y2 receptors peripheral to the blood-brain barrier plays an essential role in mediating satiety responses to gastric delivery of protein and long-chain triglycerides but not polysaccharide.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our results showed that 1) Y2 receptor blockade reversed the anorexic response to iv infusion of PYY(3-36) but did not increase food intake when administered alone; 2) Y1 and Y5 receptor antagonists neither attenuated PYY(3-36)-induced anorexia nor altered food intake when given alone; and 3) Y2 receptor blockade attenuated anorexic responses to gastric infusions of lower doses of casein hydrolysate and long-chain triglycerides but not to maltodextrin infusions. Previous work showed that Y2 antagonist BIIE 0246 does not penetrate the blood-brain barrier (13). Together, these results support the hypothesis that gut PYY(3-36) action at Y2 receptors peripheral to the blood-brain barrier plays an essential role in mediating satiety responses to gastric delivery of protein and long-chain triglycerides but not polysaccharide.…”
Section: Discussionsupporting
confidence: 77%
“…The present study further supports this hypothesis. Intravenous infusion of Y2 receptor antagonist BIIE 0246, which does not readily penetrate the blood-brain barrier (13), attenuated anorexic responses to iv infusion of PYY and to gastric infusions of casein hydrolysate and long-chain triglycerides but not maltodextrin. Together, these results suggest that gut PYY(3-36) action at Y2 receptors peripheral to the blood-brain barrier plays an essential role in mediating satiety responses to gastric delivery of protein and long-chain triglycerides but not polysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, we hypothesized that the elevated plasma NPY might negatively influences BRS and cardiac function via activation of Y1R and Y2R in DM. With the consideration that they could not cross the blood brain barrier, we employed BIBP 3226 and BIIE 0246 as Y1R and Y2R antagonists respectively [26,27]. Based on the essential role of lipid metabolism in cardiovascular dysfunction of DM, we measured the plasma lipid concentration and found that BIBP 3226 and BIIE 0246 rescued the aberrant lipid level.…”
Section: Discussionmentioning
confidence: 99%
“…Current therapeutic options are: (i) intranasal NPY delivery: to circumvent degradation in the gastrointestinal tract and to deliver peptide directly to the CNS; and (ii) novel blood-brain barrier penetrant nonpeptide Y2 antagonists that are currently being developed and tested. [165][166][167] The clinical utility and potential adverse effect profiles remain to be determined. Thus, there is a critical need for collaborative efforts in this area for design, development and preclinical testing of new agents as they become available.…”
Section: Npy Therapeutics Treatment Optionsmentioning
confidence: 99%